2015
DOI: 10.1002/aenm.201500829
|View full text |Cite
|
Sign up to set email alerts
|

Charge Accumulation and Hysteresis in Perovskite‐Based Solar Cells: An Electro‐Optical Analysis

Abstract: cell (i.e., mesoscopic, meso-superstructured and planar heterojunctions), the power conversion effi ciencies (PCEs) of these cells have improved tremendously from 3.8% to 20% within a few years. [1][2][3][4][5][6][7] The high effi ciencies obtained with the hybrid perovskites are attributed to the high absorbance and long-range balanced charge transport lengths within the hybrid perovskites. [ 8,9 ] While most studies focus on improving the device performance, equal emphasis should also be given to the fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
172
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(179 citation statements)
references
References 45 publications
(101 reference statements)
6
172
1
Order By: Relevance
“…[189] Li et al [115] also mentioned the often-observed kinks illustrated in Figure 6 in the J-V curve measurement. Several groups have observed a similar behavior, [15,117,128,190,191] and this phenomenon especially prevails when using fast scan rates. In the context of the ion-migration model, the authors found an explanation for this kink in the J-V curve.…”
Section: Modulation Of the Energetic Environment At Interfacesmentioning
confidence: 66%
“…[189] Li et al [115] also mentioned the often-observed kinks illustrated in Figure 6 in the J-V curve measurement. Several groups have observed a similar behavior, [15,117,128,190,191] and this phenomenon especially prevails when using fast scan rates. In the context of the ion-migration model, the authors found an explanation for this kink in the J-V curve.…”
Section: Modulation Of the Energetic Environment At Interfacesmentioning
confidence: 66%
“…Both the perovskite absorber layer and the interfaces between the perovskite and the charge extraction layers can have a significant impact upon the long-term stability of the solar cell. [11][12][13][14][15][16] All commercial solar modules are encapsulated in order to enable 25 years of operation. Silicon modules have historically been encapsulated with a polymer back sheet laminated with a hot-melt polymer foil to a glass front sheet, and are moving toward glass-glass laminates to deliver improved stability.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
“…Previous studies suggest that electron accumulation, arising from inefficient charge transfer at perovskite interfaces, exaggerates current voltage hysteresis and that the main origin is a combination of both defect sites responsible for trap-assisted recombination and mobile ionic species. [13,15,16] C 60 or other fullerene derivatives are already known to be able to effectively passivate or inhibit the formation of defect states at the perovskite surface. [43,44] It may be that the n-doping of C 60 further assists, by reducing the density of "vacant" trap sites in the perovskite absorber layer in the vicinity of this interface, by inducing electron accumulation within the perovskite film in this region by surface charge transfer.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
“…35,36 According to recent reports, the charge/ion accumulation at TiO 2 /perovskite interface is intimately responsible for the hysteresis response of the devices. 37,38 Before exploring the charge/ion accumulation mechanism in the devices, the key parameters of solar cells such as series resistance (R S ), diode ideality factor (m) and dark reverse saturation Considering the fact that hysteresis phenomena may be related to the interfacial charge accumulation and is more prominent in MAPbI 3 (s) than MAPbI 3 (m) devices, impedance spectroscopy (IS) measurements were performed at zero bias under dark and illumination to investigate the ionic and electronic charge accumulation. As shown in Figure S8, Nyquist spectra in the dark exhibit a high frequency semicircle related to the electronic transport followed by the low frequency line due to ionic diffusion or ionic charge accumulation.…”
mentioning
confidence: 99%